Handbook of rheological additives - Wypych, George (ChemTec Publishing, 2022)
"Only a few books were ever published on rheological modifiers, with the last one published 20 years ago. This book contains all relevant research data on the subject available to date, and it is published together with the Databook of Rheological Additives, including data of commercial and generic additives used in end-products available in the market."--